Engagement of husbands in a maternal nutrition program substantially contributed to greater intake of micronutrient supplements and dietary diversity during pregnancy: Results of a cluster-randomized program evaluation in Bangladesh - Nguyen, Phuong Hong; Frongillo, Edward A; Sanghvi, Tina; Wable, Gargi; Mahmud, Zeba; Tran, Lan Mai; Aktar, Bachera; Afsana, Kaosar; Alayon, Silvia; Ruel, Marie T; Menon, Purnima (Oxford Academic, 2022)
This article was published in the Journal of Nutrition, Oxford Academic [© 2018 American Society for Nutrition. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at: https://doi.org/10.1093/jn/nxy090 The Journal's website is at: https://academic.oup.com/jn/article/148/8/1352/5040613?login=false